Dynamic Expressions of TIGIT on Splenic T Cells and TIGIT-Mediated Splenic T Cell Dysfunction of Mice With Chronic Toxoplasma gondii Infection - Li, Haoran; Zhang, Jing; Su, Changwei; Tian, Xiaowei; Mei, Xuefang; Zhang, Zhenchao; Wang, Mingyong; Li, Xiangrui; Wang, Shuai (Frontiers in Microbiology, 2021)
As an immunosuppressive receptor, T-cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) play a critical part in cellular immune regulation mediated by pathogen infection. Whereas, TIGIT expression on splenic T cells in hosts infected with Toxoplasma gondii cysts has not been studied. In this study, we detected TIGIT expression and the changes of immune function in the spleen by flow cytometry and real-time PCR (RT-PCR). We found that TIGIT expression on splenic T cells increased significantly post infection. At the same time, splenic TIGIT+TCM cells were activated and transformed into TIGIT+TEM cells during the infection, and the cytotoxicity of TIGIT+ T cells was reduced in the later stage of infection. This study shows that chronic T. gondii infection can upregulate TIGIT expression on the surface of T cells and affect immune cell function.